The Ethics of Informed Consent for Data Registries: Moving Beyond Moral Minimalism to the High Ground. - Chingarande, George Rugare (Bioethics, 2025)
There is a rapid increase in disease registries all over the world, propelled by innovations in electronic health records and computer technologies. Unlike the developed world, where many registries are well established, many disease registries in the developing world are still in their incipient stage. Establishment of disease registries is blighted by many ethical concerns. These include but are not limited to data capture and data transfer happening without explicit patient consent; data sharing with third parties for various purposes including research, policy making and advocacy; and retrospective consent waiver. This is compounded by the lack of ethical guidelines and international best practices. This paper presents an ethical analysis of the ethics of informed consent for data registries.